Calpain-2 protein influences chikungunya virus replication and regulates vimentin rearrangement caused by chikungunya virus infection - Li, Jia; Zheng, Kang; Shen, Huilong; Wu, Hua; Wan, Chengsong; Zhang, Renli; Liu, Zhimin (Frontiers in Microbiology, 2023)
Chikungunya fever (CHIF), a vector-borne disease transmitted mainly by Aedes albopictus and Aedes aegypti, is caused by Chikungunya virus (CHIKV) infection. To date, it is estimated that 39% of the world’s population is at risk of infection for living in countries and regions where CHIKV is endemic. However, at present, the cellular receptors of CHIKV remains not clear, and there are no specific drugs and vaccines for CHIF. Here, the cytotoxicity of calpain-2 protein activity inhibitor III and specific siRNA was detected by MTT assays. The replication of CHIKV was detected by qPCR amplification and plaque assay. Western blot was used to determine the level of the calpain-2 protein and vimentin protein. Immunofluorescence was also operated for detecting the rearrangement of vimentin protein. Our results indicated that calpain-2 protein activity inhibitor III and specific siRNA might suppress CHIKV replication. Furthermore, CHIKV infection led to vimentin remodeling and formation of cage-like structures, which could be inhibited by the inhibitor III. In summary, we confirmed that calpain-2 protein influenced chikungunya virus replication and regulated vimentin rearrangement caused by chikungunya virus infection, which could be important for understanding the biological significance of CHIKV replication and the future development of antiviral strategies.